2017
DOI: 10.1371/journal.pone.0185658
|View full text |Cite
|
Sign up to set email alerts
|

Normal mode-guided transition pathway generation in proteins

Abstract: The biological function of proteins is closely related to its structural motion. For instance, structurally misfolded proteins do not function properly. Although we are able to experimentally obtain structural information on proteins, it is still challenging to capture their dynamics, such as transition processes. Therefore, we need a simulation method to predict the transition pathways of a protein in order to understand and study large functional deformations. Here, we present a new simulation method called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 45 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…Afterward, we examine how the BTS-ligand could affect the communication efficiency in the inter-residue network of the lysozyme receptor in the unbound and bound state (i.e., in the absence and presence of the BTS-ligand). To this end, we carried out an elastic network approach (ENM models) by regarding the local perturbations induced by the BTS-ligand in the C(α)-residue network that forms the lysozyme binding site [ 44 , 45 , 46 ]. In this instance, the local perturbations are propagated like an allosteric signal pathway across the communication network composed by C(α)-atom nodes which represent the residues and the network edges representing their mutual contacts connected by the two associated C(α)-residue nodes within a distance of 5.0 Å between C-alpha atoms in the lysozyme receptor structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, we examine how the BTS-ligand could affect the communication efficiency in the inter-residue network of the lysozyme receptor in the unbound and bound state (i.e., in the absence and presence of the BTS-ligand). To this end, we carried out an elastic network approach (ENM models) by regarding the local perturbations induced by the BTS-ligand in the C(α)-residue network that forms the lysozyme binding site [ 44 , 45 , 46 ]. In this instance, the local perturbations are propagated like an allosteric signal pathway across the communication network composed by C(α)-atom nodes which represent the residues and the network edges representing their mutual contacts connected by the two associated C(α)-residue nodes within a distance of 5.0 Å between C-alpha atoms in the lysozyme receptor structure.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, the local perturbations are defined by the collective anisotropic fluctuations generated from the intra-segment C α -C α atomic residue distances (labelled by the color intensity in the 2D-perturbation matrix) by the presence of a given ligand (i.e., the best-crystallographic binding pose of the BTS-ligand) which could affect the function and conformational properties of the binding residues of lysozyme. In this context, both the unbound and bound state are fully defined by the local perturbation response 3 N × 3 N Hessian matrix ( H i,j ) which describes the inter-residue allosteric communication pathway in the lysozyme [ 44 , 45 , 46 ]. Its N -elements (1 ≤ i, j ≤ N ) are the second derivatives of the anisotropic network potential (V lysozyme or V lysozyme+ligand ) which describes the (3 N )- XYZ -displacements ( ) of all the ( i , j )-residue pairs sensors ( i ) and effectors ( j ) in N -blocks of three dimensions each, and where γ R = γ L = 0.5 is an interaction constant, in the absence (lysozyme unbound state), and upon interactions (or perturbations as lysozyme plus BTS in the bound state) following the Equations (8) and (9): …”
Section: Resultsmentioning
confidence: 99%
“…In the examples above, to reproduce transitions between two structures, we used one structure as the reference and the other as the initial condition. This is of course a crude simplification, and smoother morphing methods have also been introduced [53,54,55,56,57]. Multiscale hybrid methods (e.g., all-atom MD and ANM-NMA [102]) have been developed, and combination with ENM-MD is possible.…”
Section: Further Improvement Of Models and Simulation Methodsmentioning
confidence: 99%
“…The nonlinear effect was formerly discussed in the context of transitions between structural states, sometimes involving partial unfolding (“proteinquake”) [52]. Attempts were made to connect (interpolate) multiple structures by iteratively applying NMA or introducing a smooth potential surface [53,54,55,56,57]. Also, ENM variants explicitly including nonlinear (higher-order) terms have been developed (e.g., nonlinear network model (NNM) [58]) and used for MD simulations (e.g., [59]).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they have extended ENI coupled to a rigid cluster model [119], in which the rigid domains of a protein are modeled as a rigid body, while the interaction between the rigid domains is described by elastic springs. A recent study by Kim et al [120] has suggested a normal mode-guided elastic network interpolation (NGENI) in such a way that low-frequency normal modes are used in the linear interpolation for obtaining an intermediate conformation.…”
Section: Conformational Change Of Proteinsmentioning
confidence: 99%